Slow Relaxation of the Magnetization on Frustrated Triangular Feiiiunits with S = 1/2ground State: The Effect of the Highly Ordered Crystal Lattice and the Counteranions ∇ - Spencer-Ossa, E; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Canon-Mancisidor, W; Canon-Mancisidor, W; Paredes-Garcia, V (American Chemical Society, 2021)
In order to understand how the different arrangements of highly ordered triangular FeIII S = 1/2 systems with various types of diamagnetic and paramagnetic anions affect their static and dynamic magnetic properties, we have obtained by solvothermal synthesis four new μ3-oxido trinuclear FeIII compounds: [Fe3O(Ac)6(AcNH2)3][BF4]·(CH3CONH2)0.5(H2O)0.5 (1-BF4), [Fe3O(Ac)6(AcNH2)3][GaCl4] (1-GaCl4), [Fe3O(Ac)6(AcNH2)3][FeCl4] (1-FeCl4), and [Fe3O(Ac)6(AcNH2)3][FeBr4] (1-FeBr4), where Ac- = CH3COO- and AcNH2 = CH3CONH2. The organization of the triangular units is very varied, from segregated stacks to eclipsed equilateral triangular [Fe3O]+ units along the c-axis with intercalated [MX4]- units. The ordering of the triangular species, together with disposition of the counteranions (intercalated or not), affects the static and dynamic magnetic properties of the [Fe3O]+ systems. Magnetic dc data also were satisfactorily fitted with a HDvV spin Hamiltonian, considering the existence of anisotropic phenomena (antisymmetric exchange and intermolecular interactions), in order to model the low-temperature region. From the antisymmetric exchange, we were able to obtain Δ(Ueff), which was used to model and rationalize the dynamic magnetic properties of these systems, reflecting that Orbach and Raman processes define the relaxation mechanism of these systems. ©